Translation and validation of the Myasthenia Gravis Activities of Daily Living Questionnaire: Latvian version - Grosmane, Arta; Roze, Ieva; Roddate, Marija; Ķauķe, Gundega; Žukova, Violeta; Glāzere, Ieva; Zolovs, Maksims; Ķēniņa, Viktorija (Frontiers in Neurology, 2024)
Introduction Our aim was to translate, adapt and validate the Myasthenia Gravis Activities of Daily Living scale into the Latvian language and to evaluate this instrument (MG-ADL-L) in terms of construct validity and reliability. Methods We enrolled patients with a confirmed MG diagnosis, who could speak Latvian fluently. We performed translation and adaptation according to the cross-cultural adaptation guidelines for self-reported measures. The patients were evaluated by a physician according to the Myasthenia Gravis Foundation of America classification (MGFA) and using the Myasthenia Gravis Composite Score (MGCS). Patients were asked to complete the MG-ADL-L and the 15-item Myasthenia Gravis Quality of Life (MGQOL15) Internal consistency was evaluated based on Cronbach’s α, reproducibility—Cohen’s weighted kappa and construct validity—Spearman’s correlation between the MG-ADL-L and the MGQOL15 and MGCS. We used the Kruskal–Wallis H test to compare the MG-ADL-L score distribution between the MGFA groups. Results 38 enrolled patients in the study. There was an acceptable internal consistency (Cronbach’s α = 0.76) and moderate to very good agreement between the test and retest scores (Cohen’s weighted kappa = 0.54 and 0.81). The MG-ADL-L showed a moderate positive correlation with the MGQOL15 (r = 0.5, p = 0.001) and the MGCS (r = 0.62, p < 0.001). There was a significant difference in MG-ADL-L scores between the MGFA groups (p = 0.007). Discussion The MG-ADL-L is a valid and reliable self-reported scale to assess and evaluate symptom severity and the impact of the disease on the lives of patients with MG.